Transitional Justice in Democratic Transition Countries: Spain as a Model (قضايا سياسية, 2025)
Transitional justice is one of the most important requirements required by post-conflict societies, as transitional justice procedures are chosen according to the circumstances of the transitional period. In Spain, the new political system was not established after Franco’s death as a result of a revolution, but rather was established according to a social contract between (the Francoist regime and the Republic) that was based on silence. He buried the past, believing that forgetting would contribute to laying the foundations of national unity Spanish society was convinced by their fear of the possibility of a return to the state of instability it witnessed during the civil war, but the silence did not continue, as the regime was subjected to internal and external pressures that questioned the success of the democratic transformation process. The research concluded that the new Spanish political system was able to activate a set of transitional justice procedures, such as Laws related to recognizing victims of terrorism and reviving historical memory, but they were not sufficient to confront the serious nature of the crimes and the damage resulting from them But at the same time, they constituted motivating factors for the continuation of democracy and societal peace during a certain period of time, without necessarily ensuring the continuous achievement of societal stability